Factors Affecting the Political Socialization of students at Al-Balqa Applied University/ Colleges of the South in Light of Some Variables - AL-Majali, Ala’a A. (Dirasat: Human and Social Sciences, 2024)
Objective: The current study aimed to identify the factors affecting the political socialization of students at Al-Balqa Applied University/ Colleges of the South (Karak, Shobak, Ma’an, Aqaba). Methods: The study used the descriptive survey method to achieve its objectives. A tool for the study was prepared in the form of a questionnaire. In its final form, it included five factors: family, university, parties, media, and friends, each of which included (6) items, and thus the tool in its final form consisted of (30) items. The study sample consisted of (316) male and female students who were selected by a simple random method. Results: The results showed that the media factor came in first place among the factors affecting political socialization, with an arithmetic average of (3.5), followed by the factors of friends, university, and family, and in fifth place came the parties factor, with the lowest arithmetic average of (3.1). Results of the independent samples t-test: There are no significant differences in the opinions of the study sample members regarding the factors affecting political socialization due to the variables (gender, academic program). Conclusion: It is necessary for political education institutions to have a clear message that is consistent with the goals for which they were created, and for this message to emerge from the goals and objectives of what various parties aim to support and enhance the concepts of political education.